OC-001 The Impact of the Introduction of Formalised Polypectomy Assessment on Training in the United Kingdom. (4th June 2013) - Patel, K; Faiz, O; Rutter, M D; Dunckley, P; Thomas-Gibson, S
Abstract : Introduction: Polypectomy is regarded as the most hazardous part of colonoscopy, accounting for the majority of procedure-associated morbidity and yet is a necessary skill for all colonoscopists. Training in polypectomy has, to date, been variable and poorly structured. Anecdotal evidence suggested poor exposure to polypectomy during training. A novel assessment tool, the Directly Observed Polypectomy Skills (DoPYS), was introduced nationally in the United Kingdom in October 2011 with the intention of both improving training and facilitating documentation of competency. Methods: The aim was to assess the impact of the mandatory introduction of the DOPyS as part of the formal colonoscopy certification process. Applications for certification in the year prior to the introduction of DOPyS were analysed retrospectively and compared with data collected prospectively for those in the following year. Data were collected on the total lifetime number of colonoscopies performed, the number of assessments for both colonoscopy and polypectomy and whether applicants had any evidence of performing polypectomy before certification of competence in colonoscopy. Results: There were 175 applicants for certification in the first year. The median number of procedures per candidate was 287. Thirty two per cent of candidates had evidence of any observed polypectomy with 7 per cent of candidates referring to training in endoscopic mucosal resection (EMR). The median number of formative colonoscopy assessments was 3 (range 0–16). In the year since DOPyS was introduced there were 150 applications for certification. The median number of procedures per candidate was 206. All of these candidates had evidence of polypectomy assessment with a median number of DOPyS of 7 (range 3–27). 89 per cent of applicants had evidence of assessed EMR. The median number of formative colonoscopy assessments in this cohort was 32 (range 9–199). There was a significant increase in the number of logged polypectomy assessments (p < 0.001), experience of EMR (p < 0.001) and formative colonoscopy assessments (p < 0.001). There was no significant difference in the total number of colonoscopy procedures performed. Conclusion: These data – the largest in the literature to date – show that structured polypectomy assessment improves trainees' documented exposure to therapeutic endoscopy as well as providing formal evidence of skills acquisition. As polypectomy plays an increasing role globally in colorectal cancer prevention, the DOPyS provides an effective means of assessing and certifying polypectomy in order to minimise the well-recognised risks associated with this technique. Disclosure of Interest: None Declared.